Effect of Supplemental Pollination, Boron Spray and Cultivar on Fruit Quality and Quantity of Olive (Olea europaea L.) - Shvan Ramzi Salih; Fakhraddin Mustafa Hama Salih (Kufa Journal for Agricultural Sciences)
This study was conducted during the 2020-2021 growing season at orchard of Horticulture Department, College of Agricultural Engineering Sciences, University of Sulaimani, Bakrajo, Iraqi Kurdistan Region, in order to investigate the effects of artificial pollination, boron application, and cultivar on some fruit quality and quantity of olive. Six selective pollinizers (Arbequina, Ashrasi, Hojiblanca, Picual, K18, Kaissy) in addition to self and air-pollination, two boron levels (0 and 200 mg.L-1) as well as two main cultivars (Sourani and Khadrawi) were used. Results showed that cultivars are relatively self-incompatible while cultivar, pollinizer, and boron recorded significant differences with regard to some studied parameters. Sourani Cultivar gave the highest percentage of final fruit set (1.96 %), self-incompatibility index (0.59), fruit weight (2.64 g), fruit volume (2.51cm3), oil content percentage (38.81%), soluble sugar content (185.74 μg/g DW),  while the lowest fruit dropping (13.56%), and the lowest acidity value (0.46%). Besides, the highest values of boron content (10.587%) were obtained Sourani cultivar. Boron sprayed with 200 mg.L-1 achieved the highest values of all studied parameters. Moreover, Arbequina, Ashrasi, and Picual pollinizers gave the best results. The dual interactions of the factors revealed that Sourani and 200 mg.L-1 boron, the two cultivars (Sourani and Khadrawi) with Arbequina, Ashrasi, Picual and Hojiblanca pollinizers, and 200 mg.L-1 boron with Arbequina, Ashrasi, Picual and Hojiblanca pollinizers gave the best results. Additionally, triple interactions of the factors indicated that the combination of the two cultivars, 200 mg.L-1 boron and Arbequina, Ashrasi, Picual and Hojiblanca pollinizers, demonstrated the best significant results.